2019
DOI: 10.14260/jemds/2019/135
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Nutrient Foramina in Human Upper Limb Long Bones

Abstract: BACKGROUND Nutrient foramina are cavities that conduct nutrient arteries and peripheral nerves on the shaft of long bones. Long bones receive most of the interosseous blood supply from nutrient arteries and sometimes through the periosteal vessels. The aim of this study was to determine the common location, direction & number of nutrient foramina of upper limb long bones. MATERIALS & METHODS This is descriptive study of a total 150 human upper limb long bones {50 humeri, 50 radii & 50 ulnae} taken from Departm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Similarly, radii had most of the nutrient foramina on the anterior surface (84.6%) followed by the posterior surface (12.8%). Challa et al 21 reported similar findings 70.0% and 30.0% in the anterior surfaces and medial border respectively. Ulnae had all their foramina on the anterior surface while Challa and Nanna 21 reported 78.4% foramina on their anterior surface only.…”
Section: Discussionmentioning
confidence: 61%
“…Similarly, radii had most of the nutrient foramina on the anterior surface (84.6%) followed by the posterior surface (12.8%). Challa et al 21 reported similar findings 70.0% and 30.0% in the anterior surfaces and medial border respectively. Ulnae had all their foramina on the anterior surface while Challa and Nanna 21 reported 78.4% foramina on their anterior surface only.…”
Section: Discussionmentioning
confidence: 61%